Strindberg's Ghost Sonata - Törnqvist, Egil (Amsterdam University Press, 2000)
Generally considered one of milestones in the development of modern drama, August Strindberg's chamber play The Ghost Sonata (1907) has variously been hailed as the first expressionist, surrealist and absurdist drama. rIn this monograph of the play as text and as performance - the first of its kind - Egil Törnqvist examines, in four chapters, the source text, various translations of it into English, the stage versions of Max Reinhardt, Olof Molander and Ingmar Bergman, and select radio and TV adaptations. In two framing chapters the background and impact of the play are illuminated. Focusing on Bergman's 1973 production, the book in addition contains a rehearsal diary and a transcription of this production. It is concluded with an annotated list of select productions.